2007
DOI: 10.3233/nre-2006-21404
|View full text |Cite
|
Sign up to set email alerts
|

Vocational outcome indicators in atypically recovering mild TBI: A post-intervention study

Abstract: Beyond issues of MTBI etiology, a key question remains the characterization and early identification of those individuals at risk of poor functional outcome. Using a retrospective analysis, the current study aimed at identifying the specific indicators related to return to work in adults with both symptomatic MTBI and functional impacts, having completed a specialized intervention program. In terms of outcome, 59.1% of the cohort (n = 110) returned to some form of work-related activity by the end of interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 31 publications
0
23
1
Order By: Relevance
“…RTW and vocational status represent one of the best indicators of real world functioning [ 11 ]. Identifying predictors for delayed RTW may help to identify those who may benefit from a follow-up rehabilitation program [ 3 , 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…RTW and vocational status represent one of the best indicators of real world functioning [ 11 ]. Identifying predictors for delayed RTW may help to identify those who may benefit from a follow-up rehabilitation program [ 3 , 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of patients who return to work still present symptoms, and recently published reviews found different predictors for functional recovery in general as compared to RTW [ 3 , 17 , 18 ]. Preinjury variables, such as education, occupational factors (job independence and decision-making latitude), and age, are well-documented predictors for RTW [ 3 , 4 , 8 , 12 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite clinical prevalence, the pathophysiology contributing to affective symptoms following dTBI is poorly understood, resulting in misdiagnosis and ineffective treatments (Van der Kolk, 2002;Collins et al, 2004;Hoge et al, 2014). Ultimately, ineffective treatment impacts a patient's ability to return to work, daily function, and social interactions; severely impairing the quality of life for both the patient and caregivers (Trahan et al, 2001;Guerin et al, 2006;van der Horn et al, 2013). Clinical and preclinical data demonstrate that dTBI causes profound lasting changes in the amygdala.…”
Section: Introductionmentioning
confidence: 99%
“…Robust evaluations of supported employment programs have been conducted mostly among individuals with severe mental illness-e.g., schizophrenia (Bond, Drake, & Becker, 2008;Burns et al, 2007;Campbell, Bond, & Drake, 2011;Guerin et al, 2006). For moderate to severe TBI, the Virginia Commonwealth University's Rehabilitation Research and Training Center offers a university-based supported employment program that is not specific to service members or veterans, but is reserved for individuals with severe disabilities who would not be able to secure gainful employment without ongoing job support; it provides permanent assistance through vocational intervention, on-thejob training and neuropsychological assessments, and behavioral modification (Wehman et al, 1993).…”
Section: High-intensity Programsmentioning
confidence: 99%